CRIME OF CORRUPTION FROM LEGAL PERSPECTIVE POSITIVE AND ISLAMIC LAW - Muslim Muslim; Afrizal Afrizal; Syahruddin Srg (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
Corruption is the act of rotten, dirty, and cheating, and from the positive Law and legal perspective Islam. corruption is an extraordinary crime and can even be categorized as transnational organized crime. However, the social reality in Indonesia and the World is that there is still a lot of corruption in Muslim countries or countries with a majority Muslim population, including Indonesia. Thus, this paper examines how Corruption is studied as a crime (jarimah) from the perspective of Islam. The research was conducted by optimizing library data and analyzing secondary data. This study shows that this criminal act of corruption does not get a single discussion in Islamic Law but is likened to theft.